Some Problems of Realization of Citizens’ Constitutional Rightsto a Favorable Environment - Vyacheslav O. Kushchii (Сибирское юридическое обозрение, 2017)
The article highlights the special role of the constitutional right of citizens to a favorable environment. The problems of compensation for damage caused to health or property as a result of environmental violations are identified. The Author conducts an analysis of federal and regional legislation affecting these legal relations, as well as legal acts, suggests ways to solve this problem.